Thermal and Mechanical Shock Testing of a Brick Wall and A Polystyrene Wall - Abderrahmane Khechekhouche; Bassou Karima; Khatraoui Seif Eddine; Labidi Sara (ASEAN Journal of Science and Engineering, 2023)
Polystyrene is one of the many novel materials being developed today. The goal of our research is to demonstrate that polystyrene is a good construction material in the El Oued region of Southeast Algeria. It can also be a strong rival for other building materials like brick. The results of our research, particularly in thermal testing, are very promising. Polystyrene is a better insulator than brick; the temperature of the polystyrene chamber varies between 26 and 27°C, whereas the temperature of the brick chamber varies between 36 and 37 °C. Polystyrene has a 5 times mechanical impact compared to brick. Despite its lack of availability in the region's markets, polystyrene is a strong rival to other materials such as brick.